Consumer Preferences for Oyster Attributes: Field Experiments on Brand, Locality, and Growing Method. (18th July 2017) - Kecinski, Maik; Messer, Kent D.; Knapp, Lauren; Shirazi, Yosef
Abstract : Oyster aquaculture has experienced tremendous growth in the United States over the past decade, but little is known about consumer preferences for oysters. This study analyzed preferences for oysters with varied combinations of brands, production locations, and production methods (aquaculture vs. wild-caught) using dichotomous choice, revealed preference economic field experiments. Results suggest significant and distinct differences in behavior between first-time and regular oyster consumers. While infrequent oyster consumers were drawn to oysters labeled as wild-caught, experienced oyster consumers preferred oysters raised via aquaculture. These findings will be valuable for growers and policymakers who invest in aquaculture to improve surrounding ecosystems.